The Prosthetic Influence and Biomechanics on Peri-Implant Strain: a Systematic Literature Review of Finite Element Studies - Julius Maminskas; Algirdas Puisys; Ritva Kuoppala; Aune Raustia; Gintaras Juodzbalys (Stilus Optimus, 2016)
Objectives: To systematically review risks of mechanical impact on peri-implant strain and prosthetic influence on stability across finite element studies. Material and Methods: An online literature search was performed on MEDLINE and EMBASE databases published between 2011 and 2016. Following keywords tiered screening and selection of the title, abstract and full-text were performed. Studies of finite element analysis (FEA) were considered for inclusion that were written in English and revealed stress concentrations or strain at peri-implant bone level. Results: There were included 20 FEA studies in total. Data were organized according to the following topics: bone layers, type of bone, osseointegration level, bone level, design of implant, diameter and length of implant, implant-abutment connection, type of supra-construction, loading axis, measurement units. The stress or strain at implant-bone contact was measured over all studies and numerical values estimated. Risks of overloading were accented as non-axial loading, misfits, cantilevers and the stability of peri-implant bone was related with the usage of platform switch connection of abutment. Conclusions: Peri-implant area could be affected by non-axial loading, cantilever prosthetic elements, crown/implant ratio, type of implant-abutment connection, misfits, properties of restoration materials and antagonistic tooth. The heterogeneity of finite element analysis studies limits systematization of data. Results of these studies are comparable with other findings of in vitro, in vivo, prospective and retrospective studies.